2022
DOI: 10.3390/ijerph19159002
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Literacy and Prevalence of Obesity, Arterial Hypertension, and Diabetes Mellitus

Abstract: Background: Health literacy (HL) is linked to many health outcomes, including self-management of chronic diseases. The aim of this study was to assess the association of health literacy with the prevalence of obesity, arterial hypertension (AH), and type 2 diabetes mellitus (T2DM). Methods: This cross-sectional, single-center study included 500 patients (42.2% male and 57.8% females; median age, 63 years (interquartile range, 42–73)) hospitalized at General County Hospital in Požega, Croatia, between July and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
4
9
2
Order By: Relevance
“…Interestingly, the study found that individuals with adequate health literacy were associated with a higher risk of overweight compared to those with limited health literacy. This finding is different from other studies [41][42], although one study did not find an association between health literacy and overweight [43]. Despite this finding, health literacy remains crucial in weight management [41][42].…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, the study found that individuals with adequate health literacy were associated with a higher risk of overweight compared to those with limited health literacy. This finding is different from other studies [41][42], although one study did not find an association between health literacy and overweight [43]. Despite this finding, health literacy remains crucial in weight management [41][42].…”
Section: Discussioncontrasting
confidence: 70%
“…Forgetfulness, confusion about the duration required for medication use, and mistrust about the overall efficacy of medication are among the reasons for non-adherence to diabetes management protocols in Middle Eastern countries (Mohiuddin, December 10, 2022). Conversely, after World War II, Taiwan faced severe poverty, but it is now the 8th largest economy in Asia and also the home of type 2 diabetes patients with more than 80% health literacy (Lovrić et al, 2022). A cross-…”
Section: Review Of Literaturementioning
confidence: 99%
“…Forgetfulness, confusion about the duration required for medication use, and mistrust about the overall efficacy of medication are among the reasons for non-adherence to diabetes management protocols in Middle Eastern countries . After World War II, Taiwan faced severe poverty which is now the 8th largest economy in Asia and also home of T2DM patients with 82% health literacy (Lovrić B, Placento H, Farčić N, et al, 2022).…”
Section: Lhl and Non-compliancesmentioning
confidence: 99%